2005
DOI: 10.1007/0-387-23178-1_8
|View full text |Cite
|
Sign up to set email alerts
|

Cost Efficient Upgrading of OPS Nodes

Abstract: Abstract:We come back on a technique to build modular switch nodes. This approach allows for a more cost effective expansion of OPS nodes. We give two example designs, showing that the method is useful only for Broadcast & Select OPS nodes when taking price decrease in function of time into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…We have used this SKOL technique on both the OPS architectures described in Section II in [15] and shown that for the B&S node architecture, it can be beneficial to use this SKOL technique under the condition that a cost reduction in function of time is taken into account. For the AWG based design however, SKOL does not help.…”
Section: B the Skol Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…We have used this SKOL technique on both the OPS architectures described in Section II in [15] and shown that for the B&S node architecture, it can be beneficial to use this SKOL technique under the condition that a cost reduction in function of time is taken into account. For the AWG based design however, SKOL does not help.…”
Section: B the Skol Techniquementioning
confidence: 99%
“…B&S. Cumulative cost in the second bit rate upgrade scenario, r=1, g=2 and p=0 15. (some values out of scale for clarity of the whole picture).…”
mentioning
confidence: 99%